PENGARUH SEARCH ENGINE OPTIMIZATION TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN NIAMARA HIJAB KABUPATEN TASIKMALAYA - Santi Nurazizah, - (2023)
The existence of the internet encourages human development in carrying out business activities, including digital marketing activities. One company that utilizes digital media is the Niamara Hijab company, which markets hijab products through its website. Product marketing through the website is very effective and able to increase sales. However, Niamara Hijab's website is rarely visited by consumers so that only a few consumers make purchase decisions. Based on this explanation, the right solution to influence purchasing decisions on the websites was search engine optimization. The goal to be achieved in this study, to find out the influence of search engine optimization on purchasing decisions in consumers of Niamara Hijab Tasikmalaya Regency. The object of this study is the Niamara Hijab Company which is engaged in fashion, especially hijab located in Cimadin, Cibatuireng Village, Karangnunggal District, Tasikmalaya Regency, West Java Province. This study used independent variable, namely search engine optimization and dependent variable, namely purchasing decisions. As for the method used, it is quantitative with a descriptive and verification approach. The output of this study is search engine optimization has a positive effect on purchasing decisions for Niamara Hijab consumers in Tasikmalaya Regency.